Diana : Portrait of a princess - Fincher, Jayne; Wade, Judy (Judith) (New York Simon & Schuster, 1998)
oyal photographer, Jayne Fincher photographs of Diana, Princess of Wales, from 1980 to her death
D., 3/01
Keywords: Diana, Princess of Whales; Princesses--Great Britain--Biography